Pandangan Islam Terhadap Manajemen Keuangan Dan Pembiayaan Pendidikan - Ulyani, AAP; Fauzi, Anis; Muin, Abdul; Gunawan, Agus; Priatna , Suherman (LEADERIA: Jurnal Manajemen Pendidikan Islam, 2023)
Such as misuse of finances to enrich oneself or corruption, application of standard financing regulations, schools are not transparent in financial matters towards the community. This research aims to describe the POAC theory regarding financial management and financing with Islamic principles or values. This research uses library research to describe theoretical ideas and is included in the qualitative research category. Primary educational data consists of book documents that are relevant to the type of discussion, while secondary data are books, journals and articles that are relevant to this research. The results of this research explain that Islamic financial management encourages the avoidance of waste and teaches people to live frugally and wisely in managing resources. Transparency and accountability in financial management are also highly upheld in an Islamic perspective. The POAC theory of financial management and education financing is linked to an Islamic perspective with the hope of producing new qualities in supervising educational institutions based on Shari'a which leads to the right path by maintaining guidelines and avoiding the prohibitions of Allah SWT.